2021
DOI: 10.3390/children8040269
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Serum Ferritin Level for Early Diagnosis and Differentiation in Patients with Kawasaki Disease with Macrophage Activation Syndrome

Abstract: We aimed to evaluate the utility of the serum ferritin level as an early screening test of Kawasaki disease with macrophage activation syndrome (KD-MAS). We analyzed the serum ferritin levels on the first day of admission and the clinical progress of patients diagnosed with complete or incomplete KD. Of the 158 patients, 5 were diagnosed with KD-MAS. Conjunctival injection was significantly more frequent in KD group (p = 0.035), although there were no significant differences in other clinical features. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…In general, the minimum value of DOR is 0, and the maximum value is infinity; a higher value of DOR suggests a better discriminatory test performance ( 46 ). All these results suggested that SF might be suitable as a potential biomarker for diagnosing KD, which is consistent with conclusions from other studies ( 20 , 47 ). Ferritin is an acute-phase reactant that is utilized in clinical practice as a serum biomarker ( 37 ), which regulates the homeostasis of serum iron, and elevated ferritin concentration signifies high levels of stored iron ( 48 ).…”
Section: Discussionsupporting
confidence: 92%
“…In general, the minimum value of DOR is 0, and the maximum value is infinity; a higher value of DOR suggests a better discriminatory test performance ( 46 ). All these results suggested that SF might be suitable as a potential biomarker for diagnosing KD, which is consistent with conclusions from other studies ( 20 , 47 ). Ferritin is an acute-phase reactant that is utilized in clinical practice as a serum biomarker ( 37 ), which regulates the homeostasis of serum iron, and elevated ferritin concentration signifies high levels of stored iron ( 48 ).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the incidence of MAS was reported to be 4.8% (3/63) in KD shock syndrome [ 24 ] and 3.2% (8/247) in incomplete KD [ 14 ], both of which have more severe clinical manifestations than typical KD. In this study, the incidence of MAS in refractory KD was 6.3%, which is similar to that found in previous studies by Roh et al [ 20 ] and Qiu et al [ 21 ] ( Table 3 ). The reported incidence of MAS is 7.0–13.0% in children with sJIA and 0.9–4.6% in children with SLE [ 9 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…These risk factors are useful for predicting IVIG resistance, but they are not useful for distinguishing refractory KD and MAS because they are found in both refractory KD and MAS patients [ 12 , 18 ]. The mortality rate of MAS in patients with KD was reported to be 13–25% [ 13 , 20 ]. To not overlook MAS, it is necessary to consider the possibility of developing MAS in patients with KD, especially those with risk factors for IVIG resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations